Water quality and potamoplankton of the river Buriganga and Gomti: A comparison - Bhuiyan, Mohammad Azmal Hossain; Khondker, Moniruzzaman (Dhaka University Journal of Biological Sciences, 2018)
The studied section of the river Buriganga besets with urban catchment contained higher values of pH, alkalinity, CO2, conductivity, TDS, SRP, SRS and NO3-N concentration compared to its counterpart, namely a section of the river Gomti having rural catchment characteristics. The mean values for a period of six months for the river Buriganga were 8.34, 1.48 meq/l, 8.49 mg/l, 686 μS/cm, 155.17 mg/l, 493 μg/l, 36.07 mg/l and 810.28 μg/l for pH, alkalinity, CO2, conductivity, TDS, SRP, SRS and NO3-N, respectively. While the same for the river Gomti was 7.86, 1.18 meq/l, 5.42 mg/l, 284.44 μS/cm, 79.91 mg/l, 188.37 μg/l, 26.41 mg/l and 203.99 μg/l, respectively for pH, alkalinity, CO2, conductivity, TDS, SRP, SRS and NO3-N. In the river Gomti, the concentration of DO was better (7.87 mg/l) compared to that of river Buriganga (5.53 mg/l). Because of a hilly origin of the river Gomti and availability of sediments in its water, the underwater light climate was poor compared to the river Buriganga. The Secchi depth recorded for Gomti and Buriganga were 0.26 and 0.54 m, respectively. Both the rivers were found diatom dominant in terms of population but the species prevailed were different. Fragillaria virescens Ralfs was the dominant diatom of the river Buriganga. Its density ranged from 6.5-11.09×105 ind/l which was the highest compared to the population of all other groups of potamoplankton. In Gomti another diatom namely, F. pinnata Ehrenberg was dominant and the density of which ranged from 8.45 - 12.65 × 105 ind/l. Community structure of the potamoplankton revealed 30 species from the river Buriganga and 22 species from Gomti. The study reveals that relatively higher concentration of nutrients prevails in the water of the river course having urban catchment characters compared to the rural ones. Dhaka Univ. J. Biol. Sci. 27(2): 191-200, 2018 (July)